Convenio TIR como dinamizador de la distribución internacional por carretera - Molina Andrango, Virginia Elizabeth (2019)
The multiple issues on the transportation field, specifically  across borders was studied; as well as the implications of the universal system TIR ( Transports Internationaux Routiers or International Road Transports) in the transit and customs controls for road transportation.  All of this in order to find proven and harmonized mechanisms to boost the International Distribution Road; and also to identify key success factors in the logistics operations to contribute to effective multimodality. The description, interpretation and analysis was made based on limited information that is spread out on the network to propose a solution that is based on the "know-how"; relating the general to specific elements; and vice versa. This means reducing the difficulties faced by carriers while offering a new international control system replacing traditional national procedures to the Customs Authorities. This will not only replace but homologate these procedures to ensure efficient collection and flow of international trade. In conclusion, to boost competitiveness, trading and economic development in a country is necessary a comprehensive strategy of international transport and distribution. This can be achieved with the implementation of an agreement with the TIR.  Allowing an effective system, efficient in time and efficient in quality for ground transportation that would provide industry competitiveness; boosting the economy; resulting in the reduction of time and costs; giving a quality service without letting any intermediate handling of the goods transfers. With the use of integrated information systems and international guarantees.